IMPLEMENTASI KEBIJAKAN PENERAPAN DISIPLIN DAN PENEGAKAN HUKUM PROTOKOL KESEHATAN COVID-19 DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI TAHUN 2021 - Agung Wahyu Pratama; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Implementation of the policy of implementing discipline and law enforcement of health protocols as an effort to prevent and control Covid-19 in Meranti Islands Regency, especially in Tebing Tinggi District. This study aims to determine the implementation of policies made by local governments in handling Covid-19, especially in the application of discipline and law enforcement of health protocols. This study uses the theory of Policy Implementation according to Edward III based on four variables, namely: Communication, Resources, Disposition, and Bureaucratic Structure. The research method used is a qualitative description, namely to describe real events but more than that, the results are expected to reveal hidden values. Sources of data used are primary data and secondary data to determine the number of informants by interview and documentation methods. The results of the study show that: 1. Communication is carried out by the Covid-19 Task Force in implementing discipline and law enforcement of health protocols, namely by conducting socialization education, both persuasively and humanely. 2 The resources in handling Covid-19 have been fully implemented, both human and financial resources. 3 The disposition in handling Covid-19 is a regional government apparatus that regulates and has responsibilities in their respective fields. 4 The bureaucratic structure, in this case, has (SOP) and the implementation of policies can work according to the applicable (SOP) and can be evaluated between each work unit according to existing (SOP). The inhibiting factors include internal and externa,l factors in implementing the policy of implementing discipline and law enforcement of the Covid-19 health protocol in Tebing Tinggi District, Meranti Islands Regency. Keywords: Implementation, Policy, Health Protocol, Covid-19